Fungicidal Activity of a Safe 1,3,4-Oxadiazole Derivative Against Candida albicans - Daniella Renata Faria; Raquel Cabral Melo; Glaucia Sayuri Arita; Karina Mayumi Sakita; Franciele Abigail Vilugron Rodrigues-Vendramini; Isis Regina Grenier Capoci; Tania Cristina Alexandrino Becker; Patrícia de Souza Bonfim-Mendonça; Maria Sueli Soares Felipe; Terezinha Inez Estivalet Svidzinski; Erika Seki Kioshima (Pathogens, 2021)
Candida albicans is the most common species isolated from nosocomial bloodstream infections. Due to limited therapeutic arsenal and increase of drug resistance, there is an urgent need for new antifungals. Therefore, the antifungal activity against C. albicans and in vivo toxicity of a 1,3,4-oxadiazole compound (LMM6) was evaluated. This compound was selected by in silico approach based on chemical similarity. LMM6 was highly effective against several clinical C. albicans isolates, with minimum inhibitory concentration values ranging from 8 to 32 µg/mL. This compound also showed synergic effect with amphotericin B and caspofungin. In addition, quantitative assay showed that LMM6 exhibited a fungicidal profile and a promising anti-biofilm activity, pointing to its therapeutic potential. The evaluation of acute toxicity indicated that LMM6 is safe for preclinical trials. No mortality and no alterations in the investigated parameters were observed. In addition, no substantial alteration was found in Hippocratic screening, biochemical or hematological analyzes. LMM6 (5 mg/kg twice a day) was able to reduce both spleen and kidneys fungal burden and further, promoted the suppresses of inflammatory cytokines, resulting in infection control. These preclinical findings support future application of LMM6 as potential antifungal in the treatment of invasive candidiasis.